Anticardiolipin antibodies in pathogenesis of infertility - Lončar Dragan (Vojnosanitetski Pregled)
Background/Aim. Antiphospholipid syndrome (APS) is an autoimmune disorder clinically characterized by arterial or venous thrombosis and/or specific obstetric complications and presence of antiphospholipid antibodies (aPL) in the serum. It occurs in 0.3% of pregnant women, while 1% of them have two spontaneous abortions. The aim of this study was to analyze the frequency of biphospholipid antibodies in pregnant women with recurrent spontaneous abortions. Methods. We analyzed 60 pregnant women who had two or more recurrent miscarriages. The control group included 60 healthy pregnant women. We analyzed titres of anticardiolipin (aCL) IgG and/or IgM with high titres (> 20 U/mL), lupus anticoagulant (LAC) antibodies and anti-beta-2 glycoprotein (b2-GP1) IgG as well as parameters of coagulation status of pregnant women. Results. Analyzing Spearman's rank correlation coefficient in a group of affected patients, we noticed a slightly positive correlation of lupus anticoagulants (LAC) with aCL antibodies of both classes, while the correlation with b2GP1 IgG was negative. Both classes of aCL antibodies and antib2GP1 IgG were in a discrete positive correlation with the given variables. In the control group, there was a lack of consistency in correlation of the study variables with LAC-aCl IgG, compared to the affected patients, and there was a standard negative coefficient of correlation with anti-b2GP1 IgG. The correlation ratio of anti-b2GP1 IgG was negative for all studied test parameters. Analysis of hemostatic parameters showed a statistically significant difference in the concentration of fibrinogen (p < 0.01) and thrombocyte count (p < 0.05) between the study and the control group of pregnant women. Lower mean values of fibrinogen (2.90 ± 0.45 g/L) and lower thrombocyte count [(179.20 ± 6.00) × 109] were found in the study group of pregnant women with secondary infertility compared to the mean values of fibrinogen (3.60 ± 0.55 g/L) and thrombocyte count [(236.05 ± 5.10) × 109] in the control group. Activated partial thromboplastin time and prothrombin time were statistically significantly prolonged (p < 0.05) in pregnant women with spontaneous abortions compared to controls, suggest anticoagulant activity. Conclusion. In pregnant women with spontaneous abortions compared to healthy pregnant women slightly positive correlation of LAC with aCL antibodies of both classes, as well as a positive correlation of aCL antibodies with antib2GP1 IgG exist. On the other hand, hemostatic parameters values suggest an anticoagulatnt status in the blood of pregnant women with spontaneous abortions.